The decision-making process in recommending electronic communication aids for children and young people who are non-speaking: the I-ASC mixed-methods study - Janice Murray; Yvonne Lynch; Juliet Goldbart; Liz Moulam; Simon Judge; Edward Webb; Mark Jayes; Stuart Meredith; Helen Whittle; Nicola Randall; David Meads; Stephane Hess (National Institute for Health Research, 2020)
Background: This project [Identifying Appropriate Symbol Communication (I-ASC)] explored UK decision-making practices related to communication aid recommendations for children and young people who are non-speaking. Research evidence related to communication aid decision-making is limited. The research aims were to increase understanding of influencers on the decision-making process in recommending electronic communication aids, and to develop guidance tools to support decision-making. An additional, post hoc aim was to evaluate the public involvement contribution to the I-ASC project. The research focused on the identification of attributes and characteristics that professionals, family members and those who use communication aids considered important in the recommendation process. Findings informed the development of guidance resources. The evaluation of public involvement focused on what could be learned from a nationally funded project with involvement from public contributors typically regarded as hard to include. Methodology: For the clinical decision-making component, the methodological investigation adopted a three-tier approach with three systematic reviews, a qualitative exploration of stakeholder perspectives through focus groups and interviews, and a quantitative investigation surveying professionals' perspectives. The public involvement evaluation adopted a mixed-methods approach. A total of 354 participants contributed to the decision-making data set, including professionals, family members, and children, young people and adults who use communication aids; 22 participants contributed to the public involvement evaluation. The literature review process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Thematic analysis and framework approach supported the analysis of qualitative data. Two stated preference surveys, a best-worst scaling and a discrete choice experiment, allowed the relative importance of factors in decision-making to be determined. Analysis was grounded in random utility theory. Public involvement: Two public involvement co-researchers, an adult using a symbol communication aid and a parent of a communication aid user, were core members of the research team. The I-ASC public involvement resulted in an additional award to evaluate the impact of public involvement across the project. Results: Factors influencing decision-making are not always under the control of the decision-makers, for example professional knowledge, referral criteria and service structure. Findings suggest that real clinical decisions contrast with hypothetical decisions. Survey responses indicated that children's physical characteristics are less important than their language, communication and learning abilities; however, during real-time decision-making, the opposite appeared to be true, with access needs featuring most prominently. In contrast to professionals' decisions, users and family members prioritise differing aesthetic attributes of communication aids. Time allocated to system learning remains underspecified. The research informed the development of decision-making guidance tools (https://iasc.mmu.ac.uk/; accessed 8 June 2020). A public involvement evaluation suggests that successful public involvement of individuals with disabilities requires significant resources that include staff time, training and personal support (https://iasc.mmu.ac.uk/publicinvolvement; accessed 8 June 2020). Future work: Further research is needed in the areas of language assessment, communication aid attributes, types of decision-making episodes and service user perspectives. These data highlight the need for mechanisms that enable public involvement co-researchers to be paid for their contributions to research bid preparation. Limitations: Individuals who benefit from communication aids are a heterogeneous group. We cannot guarantee that this study has captured all relevant components of decision-making. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 8, No. 45. See the NIHR Journals Library website for further project information.